2020
DOI: 10.1089/bioe.2019.0021
|View full text |Cite
|
Sign up to set email alerts
|

Intense Pulsed Electric Fields Denature Urease Protein

Abstract: Background: This article describes the effects of nanosecond pulsed electric fields (nsPEFs) on the structure and enzyme activity of three types of proteins. Materials and Methods: Intense (up to 300 kV/cm) 5-ns-long electrical pulses were applied for 500 times at 3 Hz to solutions of lysozyme, albumin, and urease. We analyzed covalent bonds (peptide bonds and disulfide bonds) of lysozyme and albumin, and also the tertiary and quaternary structures of urease as well as urease activity. Results: The results ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Summarising, this study demonstrates that EFs of different biologically relevant strengths change S of SARS-CoV-2 both at nanometre and sub-nanometre scales. Considerable changes in the secondary structure of the RBD in the wild type and currently dominant mutants of S occur at field strength orders of magnitude smaller than for most proteins [24][25][26][27][28][29][30][31][32] . We conclude that the spike protein of SARS-CoV-2 (and especially its RBD) is unusually vulnerable to external electric fields.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Summarising, this study demonstrates that EFs of different biologically relevant strengths change S of SARS-CoV-2 both at nanometre and sub-nanometre scales. Considerable changes in the secondary structure of the RBD in the wild type and currently dominant mutants of S occur at field strength orders of magnitude smaller than for most proteins [24][25][26][27][28][29][30][31][32] . We conclude that the spike protein of SARS-CoV-2 (and especially its RBD) is unusually vulnerable to external electric fields.…”
Section: Discussionmentioning
confidence: 97%
“…It has been theoretically predicted and experimentally demonstrated that static and timedependent electric fields (EFs) are capable of inducing conformational changes [25][26][27][28][29][30] or even irreversible damage in proteins [31][32][33] . The fact that extremely intense EFs of strengths larger than 1Volt per nanometre (10 9 V m⁻¹) can denature entire proteins and even break chemical bonds is trivial and of little biological relevance.…”
mentioning
confidence: 99%
“…Applying 10 6 V/cm on a protein crystal results in faint structural changes . However, experimentally, lower electric fields can have deleterious consequences on protein structure or activity, either fields of 5–50 × 10 3 V/cm applied during a few microseconds ,, or 50–500 V/cm applied through minutes to hours. , Frictional forces due to electrophoretic motion of the corresponding purified proteins might be the cause of these observations . These scenarios do not correspond to the common pulsing protocols used for electroporation delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Although providing exquisite atomistic details, that experiment was performed on a protein crystal, so its relevance to proteins under physiological condition (in solution) is limited. In solution, Urabe et al have shown that a train (500) of 5 ns, 3 MV/m electric pulses can physically denature urease [55] and a train (1000) of 1 ns, 200 MV/m pulses promotes the disintegration of transthyretin amyloid [56] . In addition, in our recent pioneering studies, we showed that an intense electric field has multiple effects on a single tubulin in vitro and in silico .…”
Section: Introductionmentioning
confidence: 99%